THE RELATIONS OF MORPHOLOGIC CHARACTERISTICS AND MOTOR ABILITIES OF JOUNG WATER POLO PLAYERS - Dragan Toskić; Ljubiša Lilić; Lazar Toskić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
The aim of our research was to determine the connection between morphologic characteristics and motor abilities of young water polo players. The sample of participants for this research can be defined as the population of water polo swimmers (N=60) aged 16 to 18, who were only included in the study under the condition that they have taken part in the water polo training process for a period of at least four years. In order to evaluate morphological characteristics of the participants we used 20 anthro¬po¬me¬tric variables (IBP) to evaluated longitudinal and transversal dimenions, mass and body voluminosity and subcutaneous fatty tissue. In this study, the measurings of the sig¬ni¬ficant motor dimensions were carried by means of the following measuring instruments which the authors (Gredelj, Hošek, Metikoš, Momirović, 1975) had previously evaluated with the help of physiological mechanisms: the integration factor, based on the me¬cha¬nism for movement structure (MSK), the synergistic automatism and tonus regulation factor (SRT); the factor for excitation intensity regulation (RIE); the excitation duration re¬gulation factor (RTE). The relations between morphological and motor dimensions we¬re determined using a canonical correlation analysis. A correlation analysis was carried out and it indicated a very high correlation between dimesions morphological cha¬ra¬cte¬ri¬stics and motor abilities of young water polo players.